Ovrednotenje tekmovalne uspešnosti smučarjev skakalcev ob upoštevanju faktorja vpliva dolžine zaletišča in vetra - Jošt, Bojan (Šport (Ljubljana), 2013)
The competitive performance of ski jumpers is a complex dependent variable defined by several independent variables. Those which are known and are already considered in the evaluation of the competitive performance of ski jumpers at the top competition level also include the variables inrun length and wind speed in a tangential direction. The purpose of the research study was to examine some aspects of the relations between both independent variables and the criterion variable of jump length. In the final single competition held on 24 March 2013 in Planica, where the 30 best ranked ski jumpers in the world cup participated, a statistically significant correlation was established (p<0.01) between the variable of wind speed in a tangential direction and flight length in both competition series. A theoretical analysis taking some practical results into account showed that the inrun factor was slightly overestimated, so the ski jumpers were slightly disadvantaged when the starting bar was heightened and gained some advantages when it was lowered. Use of the current linear model is hypothetically increasingly problematic when calculating correction points due to the effect of the wind. As shown by some theoretical arguments, a non-linear model of the calculation of correction points would be more appropriate. It is more practical when the wind speed is high, exceeding 1 m/s.
Keywords: competitive performance; faktor dolžine zaletišča; faktor vpliva vetra; inrun length factor; ski jumping; smučarski poleti; sport; šport; tekmovalna uspešnost; wing factor